(untitled) (Belügyi Szemle, 2024)
Aim: In this study, the Author reviews the criminal statistics indicators of sexual crimes. Sexual crimes can be grouped according to several classification systems – for example, the age of the victims, or the method of execution, or in light of whether they are committed with violence. Based on the latter, distinguished between violent and non-violent situations – a good example of the former is the crime of sexual violence, while the latter is child pornography. The analysis of the statistical data provides insight into how and to what extent the prevalence of sexual crime develops, as well as how and with what prevention campaigns these frequency indicators can be reduced. Methodology: In the study, the Author makes a statistical presentation, the sources of which are international and domestic crime statistics databases. Findings: Although the number of proceedings initiated for sexual crimes in Hungary can be considered average for the Central and Eastern European region, the numbers of cases detected are still at high levels. In order for these cases to decrease, programs are needed that effectively combat the effects of sexual violence myths, the fear of victim blaming, and stigmatisation. Value: This study is an overview that aims to present a complex statistical point of sexual crimes, which can serve as a basis for further comparative analyses.